Efficacy and cost‐effectiveness analysis of pretreatment percutaneous endoscopic gastrostomy in unresectable locally advanced esophageal cancer patients treated with concurrent chemoradiotherapy (GASTO 1059) - XinLei Ai; PengXin Zhang; XinMin Xie; Bo Qiu; YuJia Zhu; Lei Zhao; Mian Xi; YingJia Wu; SuPing Guo; JinYu Guo; FangJie Liu; DaQuan Wang; et al. (Cancer Medicine, 2023)
Abstract Background We launched a single‐arm phase II study to determine the efficacy and cost‐effectiveness of percutaneous endoscopic gastrostomy (PEG) before concurrent chemoradiotherapy (CCRT) in patients with esophageal squamous cell carcinoma (ESCC). Methods Eligible patients received pretreatment PEG and enteral nutrition during CCRT. The primary outcome was the change of weight during CCRT. The secondary outcome included nutrition status, loco‐regional objective response rate (ORR), loco‐regional progression‐free survival (LRFS), overall survival (OS), and toxicities. A 3‐state Markov model was applied for cost‐effectiveness analysis. Eligible patients were matched and compared with those who had nasogastric tube feeding (NTF) or oral nutritional supplements (ONS). Results Sixty‐three eligible patients received pretreatment PEG‐based CCRT. The mean change of weight during CCRT was −1.4% (standard deviation, 4.4%), and after CCRT, 28.6% of patients gained weight and 98.4% had normal albumin levels. The loco‐regional ORR and 1‐year LRFS were 98.4% and 88.3%. The incidence of grade ≥3 esophagitis was 14.3%. After matching, another 63 patients were included in the NTF group and 63 in the ONS group. More patients gained weight after CCRT in the PEG group (p = 0.001). The PEG group showed higher loco‐regional ORR (p = 0.036) and longer 1‐year LRFS (p = 0.030). In cost analysis, the PEG group showed an incremental cost‐effectiveness ratio of $3457.65 per quality‐adjusted life‐years (QALY) compared with the ONS group with a probability of cost‐effectiveness of 77.7% at the $10,000 per QALY willingness‐to‐pay threshold. Conclusion Pretreatment PEG is associated with better nutritional status and treatment outcome in ESCC patients treated with CCRT compared with ONS and NTF. Pretreatment of PEG can be cost‐effective because of its significant clinical benefits.